An Analysis of Factors Affecting the Creation of Tension and Chaos among Nurses (Case Study: Public and Private Hospitals of Yazd Province) - Gholamreza Bordbar; Reza Ebrahimzadeh Pezeshki (Shahid Sadoughi University of Medical Sciences, 2019)
Introduction: Tension and chaos are considered as a socioeconomic phenomenon that can have adverse effects on individuals, organizations, and the community if not properly managed. Therefore, this study was aimed to investigate the factors affecting the formation of tension and chaos among nurses of Yazd Province, Iran. Methods: This exploratory mixed methods research was conducted on nurses selected from 10 out of 31 hospitals of the province through cluster sampling and proportionate stratified random sampling. Data were collected using interview and a researcher-developed questionnaire. In total, 376 individuals were enrolled. The validity of the questionnaires was evaluated by face and content validity, and its reliability was verified using Cronbach's alpha test. Results: Out of 47 factors identified, 44 factors explained 70% of the tension construct. These factors were classified into seven categories and confirmatory factor analysis was used to verify the construct validity of the categories. The results showed acceptable initial clustering. Moreover, financial and economic factors, work conditions and job security were identified as the most important factors for explaining the studied construct. Conclusion: Given the issues discussed and viewpoints expressed about the seven categories identified regarding the strike by hospital directors, human resources area must be paid special attention and measures beyond changing the name of the administrative unit to human resources or human capital must be taken.